INTERNALISASI KODE ETIK PROFESI GURU PADA ERA DIGITAL: IDENTIFIKASI TANTANGAN DAN REKOMENDASI STRATEGI PENGUATAN KOMPETENSI PROFESIONAL - Mega Fadilah; Mohammad Ridho; Shyeftya Nurdyan; Nur Khasanah (STKIP Subang, 2026)
The use of digital technology in education has brought significant changes to how teachers carry out their professional duties. However, not all teachers are ready to face the ethical challenges that arise in digital spaces. This study aims to identify the challenges of internalizing the professional code of ethics for teachers in the digital age and to recommend strategies to strengthen teacher professional competence. The method used is a systematic literature review (SLR) based on the PRISMA 2020 guidelines, using sources from Google Scholar, Scopus, ERIC, DOAJ, and Garuda Kemdikbud published in 2015–2024. From 94 initial sources, 46 were selected through a three-stage screening process. The results show five main challenges: the digital divide, ambiguity of ethical norms in virtual spaces, weak oversight mechanisms, changes in teacher-student interaction patterns, and the erosion of professional identity through social media. Five strengthening strategies are recommended: revitalizing the teacher education curriculum, developing a culture of reflection through communities of practice, integrating digital ethics into continuous professional development, updating the code of ethics, and empowering transformational school leadership. This study contributes to discussions on teacher professional ethics in Indonesia, particularly in the context of digital education that is still relatively understudied.